Spatiotemporal variation of household water consumption and coping strategies in water-stressed city of arid and semiarid Northwest China - Dang, Xiaohu; Li, Lin; Fan, Liangxin (Frontiers in Environmental Science, 2022)
With the increasing water demand of population growth and urbanization, cities in arid and semi-arid China are facing increasingly severe water scarcity. Understanding the spatio-temporal patterns of water consumption and its driving factors is of importance to formulate public policy and alleviate urban water crisis. In this study, spatio-temporal variations of water consumption of 42 cities in Northwest China are identified and their influencing factors are determined by cluster tree analysis and factor analysis. The results show that per capita domestic water consumption is decreased by 9.5% from year of 2003 to 2020 with significant spatio-temporal variations of medium consumption city (86.87-193.66 L/d per capita per day) decreased and low (<86.87 L/d per capita per day) and high consumption city (>193.66 L/d per capita per day) increased. The influencing factors varied across three type cities. For low and high consumption cities, increasing of capacity of water supply and popularize of wash machines are the main reasons for the growth of water consumption, while for medium consumption cities the implement of water saving activities and improvements of reuse rate are the main reasons for reduction of water consumption. The findings of this work suggested that improving water saving applicances and water-use efficiency in high water consumption cities and increasing water supply capacity in low water consumption cities should be considered in urban sustainable water management strategies in Northwest China.